Sistema de medição capacitivo para determinação da fração de vazio em escoamentos bifásicos - Libert, Nikolas (2013)
Two-phase flows are not only present in environmental phenomena such as clouds, but are found widespread in industrial applications. Such flows may be described as the stream of two immiscible substances, called phases, in a pipe or vessel. Most usual type of flow is gas-liquid flow and it can be found in chemical, nuclear, power generation, petroleum, and space industry. The study and characterization of such flows are important both in the realization of projects as in the monitoring and control of the facilities in which they occur. An important parameter in flow characterization is the void fraction, which indicates the volumetric amount of gas in gas-liquid flows. The gaseous and liquid phases in a flow usually present different electric properties, such as conductivity and permittivity. If electrodes are arranged around a pipe, they may form a capacitor whose capacitance depend upon the flowing mixture properties and their spatial distribution. The main goal of this work is to develop a non-invasive capacitive probe for void fraction determination in two-phase flow. It describes the assembly of the electrodes, the development of hardware for capacitance measurement, and the development of software that provides access to the measurement data obtained by the hardware. The response of capacitive sensors depends not only on void fraction values, but also on the flow pattern, that is, on the way that phases are distributed inside the pipe. Due to this fact, electric field simulations of the sensor’s response at different flow patterns were performed. Based on the results of the simulations and on the measurement results, void fraction values for air-water flow at controlled conditions was calculated and comparatively evaluated. The results obtained show the good performance of developed capacitive probe which may now be deployed in two-phase flow studies.